Desenvolvimento e análise da eficiência energética de um sistema de automação de precisão para irrigação localizada utilizando arduino e inversor de frequência - Pereira, Francisco Aécio de Lima (Universidade Federal Rural do Semi-Árido, 2017)
The rate of growth of the world's population declines, but nonetheless continues to grow considerably, making water and energy resources increasingly limited. To become viable over time, irrigation, which is the largest consumer of fresh water and a large consumer of energy, needs to be increasingly efficient. One of the ways to improve this framework is the use of technologies. The objective of this work was to develop a precision automation system to control the service pressure in localized irrigation. A test bench was built consisting of a water reservoir, a three-phase motor pump (380 V), hydraulic valves and a commercial electronic controller for opening and closing valves. The commercial irrigation controller opened and closed the valves every 20 mim, which were adjusted so as to insert an increasing load loss from valve 1 to 6. Two tests were performed with distinct drives, one using the automated system, in which the Pump was made by the converter frequency, and the second test using direct power from the electric power grid. And the second test using direct mains power supply. The automated system consisted of an Arduino Mega board that controlled the converter frequency, monitored and recorded rotational data, power and return line pressures, status of each valve (open or closed) and date and time of the test. In automatic mode, the system worked in a closed loop, monitoring the process variables and acting on the converter frequency to change the pump speed and, consequently, to adjust the output pressure of the valves to the previously programmed value, maintaining the pressure of Constant output. In the direct drive of the network, the system worked in open loop, and the Arduino board only monitored and recorded the process variables. Electrical and hydraulic parameters were analyzed from the automatic mode with converter frequency and compared with a conventional system directly driving the electric network. The results showed that the Arduino board satisfactorily controlled the outlet pressure when using the converter frequency. The rotation in the automatic mode varied from 2,924 to 3,646 rpm, corresponding to a frequency variation of 49.67 to 62.29 Hz respectively, as well as reducing the active power by 42.8%. For the direct drive of the network, the engine speed was 3,519  4.64 rpm, with a low active power variation of 2,320,55  87,54 W. On valve 6, for the automatic system, the frequency and rotation parameters Were above that specified for the engine 62.29 Hz and 3,646 rpm. Comparing both drive systems to valve 5, which is the direct balance point of the electric grid with the automatic system, it was observed that in the electric grid the active power was 11,728.70 W and in the automatic mode was 8,341, 01 W. Regarding the automatic mode, the reduction was 40.61%. The apparent power and the inductive reactive in absolute terms rose from valves 1 to 6, but if we analyze in relation to the active power it reduced, indicating that the system became more efficient, as a consequence the power factor rose from 0.52 to 0, 67
Keywords: Agricultura irrigada; Controle de pressão; Potência ativa; Válvula hidráulica; Controlador de irrigação; Irrigated agriculture; Rotation variation; Active power; Hydraulic valve; Irrigation controller; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO